The Effect of the Incorporation Level of Rosa rugosa Fruit Pomace and Its Drying Method on the Physicochemical, Microstructural, and Sensory Properties of Wheat Pasta - Grażyna Cacak-Pietrzak; Agata Marzec; Aleksandra Rakocka; Andrzej Cendrowski; Sylwia Stępniewska; Renata Nowak; Anna Krajewska; Dariusz Dziki (Molecules)
This study investigated the effects of the addition of Rosa rugosa fruit pomace and drying methods on the properties of pasta, such as culinary properties, color, texture, microstructure, phenolics, antioxidant capacity, and sensory properties. In laboratory conditions, the pasta was produced using low-extraction wheat flour with the addition of pomace at 0, 2, 4, 6, and 8% (g/100 g flour) and dried using either convective or microwave–vacuum drying. The incorporation of pomace into the pasta caused a notable reduction in lightness and increased redness and yellowness, as well as a decrease in pasta hardness and sensory acceptability. The RFP addition also increased the polyphenol content and antioxidant potential. The microwave–vacuum drying resulted in pasta with shorter cooking times, lower cooking loss, and higher total phenolic content and antioxidant activity compared to convective drying. Although the drying method did not markedly affect sensory attributes, ultrastructural analysis revealed that samples subjected to convective drying had a more compact structure, while microwave–vacuum dried pasta exhibited larger pores and smaller starch granules. Total porosity was higher in microwave–vacuum dried pasta. Taking into account both the level of pomace enrichment and the drying technique, the most optimal outcomes were achieved when microwave–vacuum drying was applied and the pomace addition did not exceed 4%.